Beryllium minerals as monitors of geochemical evolution from magmatic to hydrothermal stage; examples from NYF pegmatites of the Trebic Pluton, Czech Republic - Zachar,A.; Novak,M.; Skoda,R. (Journal of Geosciences, 2020)
Mineral assemblages of primary and secondary Be-minerals were examined in intraplutonic euxenite-type NYF pegmatites of the Trebic Pluton, Moldanubian Zone occurring between Trebic and Vladislav south of the Trebic fault. Primary magmatic Be-minerals crystallized mainly in massive pegmatite (paragenetic type I) including common beryl I, helvite-danalite I, and a rare phenakite I. Rare primary hydrothermal beryl II and phenakite II occur in miarolitic pockets (paragenetic type II). Secondary hydrothermal Be-minerals replaced primary precursors or filled fractures and secondary cavities, or they are associated with ,,adularia” and quartz (paragenetic type III). They include minerals of bohseite-bavenite series, less abundant beryl III, bazzite III, helvite-danalite III, milarite-agakhanovite-(Y) III, phenakite III, and datolite-hingganite-(Y) III. Chemical composition of the individual minerals is characterized by elevated contents of Na, Cs, Mg, Fe, Sc in beryl I and II; Na, Ca, Mg, Fe, Al in bazzite III; REE in milarite-agakhanovite-(Y) III; variations in Fe/Mn in helvite-danalite and high variation of Al in bohseite-bavenite series. Replacement reactions of primary Be-minerals are commonly complex and the sequence of crystallization of secondary Be-minerals is not defined; minerals of bohseite-bavenite series are mostly the latest. Beryl usually occurs in pegmatites with rare tourmaline, whereas helvite-danalite bearing pegmatites are tourmaline-rich. Abundant tourmaline in pegmatites with helvite-danalite and its scarcity in beryl-bearing pegmatites indicate that early tourmaline crystallization affected activity of Al in the parental medium and thus may have controlled formation of primary Be-minerals (beryl - higher Al, helvite-danalite - lower Al) which crystallized later. Secondary Be-minerals with dominant minerals of bohseite-bavenite series and milarite suggest high activity of Ca in fluids. Variations in chemical composition (Al contents) of bohseite-bavenite series were controlled by the chemical composition of the precursor. High variability of primary magmatic Be-minerals within a single pegmatite district is exceptional and it is constrained by variable activities of Si and mainly Al, divalent cations - Ca, Mn, Fe, Zn and Mg, trivalent cations - REEs, Sc, and B, S, and fO2 in the individual pegmatites.
Keywords: beryl; phenakite; helvite-danalite; milarite- and gadolinite-group minerals; bohseite-bavenite; NYF pegmatites; Trebic Pluton